1981
DOI: 10.1002/bbpc.19810851118
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Clusters in 1‐Propanol/Water‐Mixtures

Abstract: and SFB 123, Im Neuenheimer Feld 256, 6900 Heidelberg Cluster-Bildung / Flhsigkeiten / Lichtstreuung Very sensitive and accurate elastic light scattering (LS) measurements have been carried out on mixtures of water with methanol, ethanol, 1-propanol and 2-propanol. Methanol showed no particular effect, while ethanol, 2-propanol and 1-propanol showed signs of increasing cluster formation at a composition of 1 alcohol molecule to 5 water molecules. For the mixture of 1-propanol with water, additional measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 8 publications
4
12
0
Order By: Relevance
“…Perhaps the jelly-like surface of the polystyrene particles promotes the formation of 1-propanol/water envelopes with approximately one mole 1-propanol and four mole water in composition. The composition of the lyospheres is very close to the value which was detected for cluster structures in binary 1-propanol/water mixtures [5]. By a simple model ( Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Perhaps the jelly-like surface of the polystyrene particles promotes the formation of 1-propanol/water envelopes with approximately one mole 1-propanol and four mole water in composition. The composition of the lyospheres is very close to the value which was detected for cluster structures in binary 1-propanol/water mixtures [5]. By a simple model ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…In mixtures of organic liquids with water, the organic molecules often have a tendency to aggregate with one another or tend to associate with water molecules in clusters. For instance, mixtures of 1-propanol or its longer-chained homologues with water can form micellelike structures of well-defined composition [5].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, adsorption of water on the surface might increase rapidly due to the very hydrophilic surface that is produced by the high surface density of hydroxyl groups from adsorbed alcohol molecules. Grossmann and Ebert [21] have found that ethanol and 1-propanol show signs of increasing cluster formation at a composition of 1 alcohol molecule to 5 water molecules. For the mixture 1-propanol-water the cluster is formed by 8 1-propanol molecules and a solvation envelope of about 40 water molecules.…”
Section: Resultsmentioning
confidence: 98%
“…This assumption seems to be correct: the highest (d 1 7 d 2 ) difference was noted in ACN and EtA, the monomers that give the maximum number of homogeneous samples (Fig. Nanostructuring occurs (owing to the``hydrophobic demixtion'') (5), followed by formation of zones with higher local concentration of hydrocarbon chains (6,8). Styrene, which is solubilized in a reduced number of systems, yields the lowest difference.…”
Section: Discussionmentioning
confidence: 96%